Reading, Writing and Learning Disorders in Dyslexic Sufferers - Gustianingsih; Ali (Universitas Pendidikan Ganesha, 2025)
Many individuals with normal or even above-average intelligence experience difficulties in reading, writing, and speaking without any apparent sensory or educational causes. This condition is known as dyslexia, which often goes undetected early on and has a negative impact on language learning processes. This study aims to conduct an in-depth analysis of the types of dyslexia, its neurological causes, and effective intervention strategies to minimize language barriers for individuals with dyslexia. The study employs a qualitative approach with a case study design. The research subject consists of one individual with dyslexia who exhibits significant difficulties in reading, writing, and speaking. Data was collected through direct observation, in-depth interviews, and documentation related to the subject's language development. Research instruments include interview guides and structured observation sheets. Data was analyzed using thematic analysis techniques to identify patterns of language disorders and their causal factors. The results of the study indicate that dyslexia is a neurological disorder that affects the left hemisphere of the brain responsible for language processing. Two types of dyslexia were identified: developmental dyslexia, which is genetic, and acquired dyslexia, which results from brain damage. Although it cannot be cured, the disorder can be minimized through intervention and specialized learning strategies. The study concluded that early diagnosis and individualized learning approaches are crucial for supporting literacy skills in individuals with dyslexia. The implications of this research emphasize the importance of teacher training and the provision of specialized pedagogical strategies for students with diverse learning needs.